Reflective Writing of New Graduate Students: Their Challenges and Experiences in an Open and Distance Education - Ridulme, Queenie R.; Sales, Rachel Anne Joyce C. (International Journal on Open and Distance e-Learning, 2019)
The study was conceptualized out of the program educators’ reflections on coping and adjustment experiences of new graduate students’ transition into their first year of learning in an open and distance education graduate program in nursing. This study explored the questions raised by students during their first year in the program and looked more closely into their experiences and coping that they did in the open and distance education mode in their written reflections during their first year in the program. The objectives of this research were to identify the challenges and learning experiences revealed in reflective assignments written by new graduate students undertaking an open and distance e-learning education in their first year in an open university in the Philippines and use the written reflections of the students to construct new strategies and practices for the development of the program for the future students.